Science, Diplomacy, and the Red Sea’s Unique Coral Reef: It’s Time for Action - Kleinhaus, Karine; Al-Sawalmih, Ali; Barshis, Daniel J.; Genin, Amatzia; Grace, Lola N.; Hoegh-Guldberg, Ove; Loya, Yossi; Meibom, Anders; Osman, Eslam O.; Ruch, Jean-Daniel; Shaked, Yonathan; Voolstra, Christian R.; et al. (Frontiers in Marine Science, 2020)
Rapid ocean warming due to climate change poses a serious risk to the survival of coral reefs. It is estimated that 70-90 percent of all reefs will be severely degraded by mid-century even if the 1.5oC goal of the Paris Climate Agreement is achieved. However, one coral reef ecosystem seems to be more resilient to rising sea temperatures than most others. The Red Sea’s reef is one of the longest continuous living reefs in the world, and its northernmost portion extends into the Gulf of Aqaba. The scleractinian corals in the Gulf have an unusually high tolerance for the rapidly warming seawater in the region. They withstand water temperature anomalies that cause severe bleaching or mortality in most hard corals elsewhere. This uniquely resilient reef employs biological mechanisms which are likely to be important for coral survival as the planet’s oceans warm. The Gulf of Aqaba could potentially be one of the planet’s largest marine refuges from climate change. However, this unique portion of the Red Sea’s reef will only survive and flourish if serious regional environmental challenges are addressed. Localized anthropogenic stressors compound the effects of warming seawater to damage corals and should be mitigated immediately. Reefs in the rest of the Red Sea are already experiencing temperatures above their thermal tolerance and have had significant bleaching, though they too would benefit from fewer local anthropogenic stressors. The countries bordering the entire Red Sea will need to cooperate to enable effective scientific research and conservation. The newly established Transnational Red Sea Center, based at the Ecole Polytechnique Fédérale de Lausanne, can serve as the regionally inclusive, neutral organization to foster crucial regional scientific collaboration.